The Effect of Using Guessing Game on Students Vocabulary Achievement at Grade VIII of MTSN 6 Agam - Ananda, Anisa; Putri, Hilma Pami; Sakti, Genta; Safitri, Loli (Education Achievement: Journal of Science and Research, 2024)
Vocabulary is a component of words with meaning and one of the most essential aspects of learning English. However, pupils are not taught vocabulary specifically in school. This results in a large number of students who lack fundamental vocabulary knowledge, despite the fact that vocabulary is one of the most essential components that students must comprehend in order to learn effectively in class. The purpose of this study was to determine whether the use of a guessing game has a significant impact on students' vocabulary achievement. This research employed a quantitative method and a quasi-experimental design; the research population was eighth-grade MTsN 6 Agam students. The sample was collected using a technique of purposive sampling. Students from the two classes, experimental class with 30 students and control class with 31 students, were given a pre- and post-test. This research instrument is a vocabulary test with 25 multiple-choice questions. The data were analyzed with SPSS 26. The calculated post-test result for the experimental class revealed a mean score of 89.47. It exceeds the mean score of the control group, which was 62.58. The standard deviation of each class is then calculated. Using Independent sample t-test, the researcher compared post-test experimental class and control class using the t-test formula. The output indicates that the value of Sig. (2-tailed) is 0.00 0.05. It indicates that Ha is acceptable. There is a substantial difference between students who are taught using Guessing game and those who are not. The result is also indicated by the fact that the mean post-test score of the experimental group (89.47) is higher than that of the control group (62.28). It indicates that students who are taught with Guessing game are superior to those who are not. Guessing game has a significant impact on the vocabulary attainment of eighth-grade MTsN 6 Agam students.